Process evaluation of a community-based program for prevention and control of non-communicable disease in a developing country: The Isfahan Healthy Heart Program, Iran - Boshtam Maryam; Bahonar Ahmad; Heidari Kamal; Alavi Mousa; Abedi Heidar; Sarrafzadegan Nizal; Kelishadi Roya; Rabiei Katayoun; Zare Karim; Sadeghi Shahryar (BMC, 2009)
Abstract Background Cardiovascular diseases are the most common cause of mortality in Iran. A six-year, comprehensive, integrated community-based demonstration study entitled Isfahan Healthy Heart Program (IHHP) conducted in Iran, and it started in 2000. Evaluation and monitoring are integrated parts of this quasi-experimental trial, and consists of process, as well as short and long-term impact evaluations. This paper presents the design of the "process evaluation" for IHHP, and the results pertaining to some interventional strategies that were implemented in workplaces Methods The process evaluation addresses the internal validity of IHHP by ascertaining the degree to which the program was implemented as intended. The IHHP process evaluation is a triangulated study conducted for all interventions at their respective venues. All interventional activities are monitored to determine why and how some are successful and sustainable, to identify mechanisms as well as barriers and facilitators of implementation. Results The results suggest that factory workers and managers are satisfied with the interventions. In the current study, success was mainly shaped by the organizational readiness and timing of the implementation. Integrating most of activities of the project to the existing ongoing activities of public health officers in worksites is suggested to be the most effective means of implementation of the health promoting activities in workplaces. Conclusion The results of our experience may help other developing countries to plan for similar interventions.